Between China and Europe : person, culture, and emotion in Macao - Pina-Cabral, João de (London School of Economics monographs on social anthropology ;, 2002)
From the mid-1500s to December 1999, Macao was the longest-standing site of economic, religious and political contact between the Chinese and European worlds. Yet this surprising capacity for survival has resulted, ironically, form the very weakness of the Portuguese presence. In particular, since the foundation of Hong Kong (in 1840), Macao had depended on a creative use of its marginality - as a centre for gambling, for the coolie trade, the opium trade, the semi-clandestine gold trade and so on. As a rear window on China, Macao provides us with fascinating examples of marginality that allow us to study the limits of the systems that characterize the Chinese world. -- Présentation de l'éditeur.